2020
DOI: 10.1097/mao.0000000000002511
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Recording of Auditory Brainstem Responses for Monitoring of Floating Mass Transducer Coupling Efficacy During Revision Surgery—Proof of Concept

Abstract: Objective: The objective of the study was to measure auditory brainstem responses elicited by stimulation via a semi-implantable active middle ear implant with an electromagnetically driven floating mass transducer to quantify the coupling efficacy (=vibroplasty in situ thresholds – bone conduction thresholds) in a patient during a revision surgery. Patients: One patient, reimplanted with an active middle ear implant in a revision surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 11 publications
0
23
0
1
Order By: Relevance
“…To provide such feedback, the VIB thresholds have to be measured objectively. It has been shown that the recording of auditory evoked potentials (AEPs), like auditory steady state responses (ASSRs) [20], compound action potentials (CAPs) [21][22][23], and auditory brainstem responses (ABR) [24][25][26] is possible in AMEI patients. Custom made set-ups were used in these studies for providing stimulation by the implanted transducer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide such feedback, the VIB thresholds have to be measured objectively. It has been shown that the recording of auditory evoked potentials (AEPs), like auditory steady state responses (ASSRs) [20], compound action potentials (CAPs) [21][22][23], and auditory brainstem responses (ABR) [24][25][26] is possible in AMEI patients. Custom made set-ups were used in these studies for providing stimulation by the implanted transducer.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the studies lack a sufficient sound- or vibration-level calibration of the set-up allowing only a relative assessment, i.e., comparing one FMT coupling position to another. However, Fröhlich et al [ 26 ] have shown that measuring VSB-evoked ABRs using the experimental set-up already described by Radeloff et al [ 21 ] was feasible to quantify the FMT coupling quality in a VSB patient undergoing revision surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Custom-made experimental set-ups were used in all studies for providing stimulus transmission by the FMT. While most studies only aimed on relative measurements, it has recently been reported that coupling efficiency could also be determined quantitatively by measuring VSB evoked ABRs ( 26 , 27 ). A modified AP404 audio processor (MED-EL, Innsbruck, Austria) programmed to preoperative BC thresholds and fitted with an insert earphone sound tube attached to the microphone aperture was used for providing stimulation by the implanted FMT.…”
Section: Introductionmentioning
confidence: 99%
“…Small differences indicate good coupling, i.e., efficient energy transmission to the inner ear without loss of energy. To determine the coupling efficiency objectively, auditory evoked potentials like auditory steady state responses (ASSRs) (19,20), compound action potentials (CAPs) (21)(22)(23), and auditory brainstem responses (ABRs) (24)(25)(26)(27) have been recorded in patients treated with a VSB. Custom-made experimental setups were used in all studies for providing stimulus transmission by the FMT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation